A cellulose composite ultrafiltration membrane and its preparation method

By designing the multi-layer structure and material combination of cellulose composite ultrafiltration membranes, the problems of poor hydrophilicity, slow flow rate and insufficient mechanical strength of existing cellulose ultrafiltration membranes are solved, and efficient retention and rapid filtration of biomolecules are achieved, thereby improving protein yield and membrane service life.

CN115569521BActive Publication Date: 2025-09-16HANGZHOU COBETTER FILTRATION EQUIPMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211330287.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-09-16
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

Existing cellulose ultrafiltration membranes have problems such as poor hydrophilicity, slow flow rate, insufficient mechanical strength and low interlayer bonding strength when separating and purifying biomolecules, which affect protein yield and filtration efficiency.

Method used

A cellulose composite ultrafiltration membrane was designed, including an ultrafiltration layer, a transition layer, a bonding layer and a substrate layer. Each layer is composed of different polymer materials. Through the design of non-directional tortuous pathways and porous structures, the hydrophilicity and fluid fluidity of the cellulose polymer are ensured, while the interlayer bonding strength and mechanical strength are enhanced.

Benefits of technology

It achieves efficient retention of 1-750K molecular weight biomolecules, improves protein yield, enhances flow rate and membrane service life, reduces pressure loss, and is suitable for long-term filtration under high pressure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115569521B_ABST
    Figure CN115569521B_ABST
Patent Text Reader

Abstract

The present invention provides a cellulose composite ultrafiltration membrane and a preparation method thereof. The ultrafiltration membrane comprises a main body, one side surface of which is a first outer surface, and the other side surface of which is a second outer surface. Along the direction of fluid flow, the main body is sequentially composed of an ultrafiltration layer, a transition layer, a binding layer and a substrate layer, and the SEM average pore size of the first outer surface is 1-80nm. The membrane is used for efficiently intercepting 1K-750K biomolecules. The ultrafiltration layer and the transition layer are formed by a cellulose polymer with strong hydrophilicity to ensure product yield. In the binding layer, the cellulose polymer forms a first fiber, and the non-natural polymer forms a second fiber. Adjacent first fibers and second fibers are separated from each other to form a gap for fluid to pass through. The non-natural polymer is any one of a sulfone polymer, nylon and polyvinylidene fluoride. The presence of the gap greatly improves the flow rate of the filter membrane, ensuring that the filter membrane can quickly separate and purify various biomolecular fluids. The preparation method provided by the present invention is convenient, fast and effective.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane materials, and more particularly to a cellulose composite ultrafiltration membrane and a preparation method thereof. Background Art

[0002] In recent years, biopharmaceuticals (particularly antibodies such as immunoglobulins) have become widely used due to their high therapeutic efficacy and minimal side effects. Biomolecules such as antibodies and viruses are primarily produced by organisms such as animal cells. Therefore, for their use as pharmaceuticals, fluids containing these biomolecules must be separated and purified. Currently, membrane separation is the most commonly used method for separating and purifying biomolecules. This is due to its high efficiency, low energy consumption, ability to operate at room temperature, minimal damage to the active ingredients (biomolecules), high biomolecule recovery rates, and high economic benefits.

[0003] The core of membrane separation technology is the separation membrane, which primarily comprises polymer membranes. These membranes are made from organic polymers using a specific process. Depending on the type of polymer, polymer membranes can be further categorized into cellulose, polyamide, sulfone, and polytetrafluoroethylene polymer membranes. Based on pore size, membranes can be further categorized into microfiltration, ultrafiltration, nanofiltration, and reverse osmosis membranes. Furthermore, membrane geometry can be further categorized into plate membranes (flat membranes) and hollow fiber membranes. Flat membranes are favored by the market due to their simple structure, high compressive strength, and suitability for various processing operations.

[0004] For example, the European patent application number EP0596411A3 applied for by the patentee EMD Millipore Corporation is a composite ultrafiltration membrane. The membrane has a resistant substrate based on microporous polyolefin or sulfone polymer and an ultrafiltration layer formed by sulfone polymer. It has good mechanical strength and a flux of 30 to 50 gfd / psi, and a fast filtration speed. However, the membrane also has certain disadvantages. The ultrafiltration membrane layer is made of sulfone polymer. Although the hydrophilicity is improved after hydrophilic treatment, its hydrophilicity is still poor compared with cellulose membrane, thereby adsorbing a certain amount of protein, resulting in too low protein yield and low economic benefits.

[0005] Furthermore, there are also ultrafiltration layers made of cellulose materials and non-woven fabrics as the base material on the market. The composite process is simple and the preparation is relatively easy. At the same time, since the ultrafiltration layer of the membrane is made of cellulose materials, the membrane has excellent hydrophilicity and extremely low protein adsorption, which is conducive to obtaining high product yields. However, such ultrafiltration membranes also have certain disadvantages, namely, the flatness of the non-woven fabric is limited, and it is easy to have some fiber structures such as burrs, which may poke into the ultrafiltration layer and then destroy the structure of the ultrafiltration layer. Once such a situation occurs, the filter holes on the ultrafiltration layer will become larger, so that the ultrafiltration layer can allow particles larger than the retention limit specified by the requirements to pass through, affecting its ultrafiltration effect.

[0006] In addition, the Chinese patent application number CN95194260.3 filed by the patentee Millipore Corporation is a cellulose ultrafiltration membrane, which comprises a microporous alkali-resistant substrate and an ultrafiltration membrane layer formed of a polymer cellulose ester or cellulose. The thickness of the ultrafiltration membrane layer is about 1-20 microns, and the distance from the polymer extending into the microporous alkali-resistant substrate is between 5-30 microns. The membrane also has a molecular weight cut-off of 500 Daltons to 1500K Daltons. By selecting a suitable substrate, such as a polyolefin membrane, the surface fibers of the substrate layer are ensured not to protrude too much, thereby ensuring that the ultrafiltration layer of the finished membrane will not be punctured by the fibers. Affects product quality; and the ultrafiltration membrane layer is made of cellulose polymer, which makes the ultrafiltration membrane have a higher protein yield; at the same time, it is observed through SEM images that part of the cellulose polymer will penetrate into the polyolefin microporous membrane, and then the fibers formed by the cellulose polymer and the fibers formed by the polyolefin will adhere to each other, ensuring the overall composite strength of the membrane; but such a membrane structure also has a problem. When the fluid passes through this area, the two mutually adhered fibers will have a strong obstruction to the flow of the fluid. This obstruction makes it impossible for the fluid to flow quickly, resulting in a significantly lower overall flow rate of the ultrafiltration membrane and a longer filtration time.

[0007] In summary, the existence of the above problems has also limited the development of ultrafiltration membranes for purifying biomolecules to a certain extent. Summary of the Invention

[0008] In view of the shortcomings of the existing technology, the purpose of the present invention is to provide a cellulose composite ultrafiltration membrane for separating and purifying biomolecules and a preparation method thereof. The ultrafiltration membrane has an ultrafiltration layer made of a cellulose polymer, thereby easily obtaining a high protein yield; at the same time, it has high efficiency in retaining substances with a molecular weight of 1-750K, and also has a faster flow rate and a short filtration time.

[0009] To achieve the above-mentioned objectives, the present invention provides the following technical solutions: a cellulose composite ultrafiltration membrane, comprising a main body, wherein the main body has a non-directional tortuous passage, one side surface of the main body is a first outer surface, and the other side surface is a second outer surface, and along the direction of fluid flow, the main body is composed of an ultrafiltration layer, a transition layer, a binding layer and a substrate layer in sequence, the ultrafiltration layer includes a first outer surface, and the substrate layer includes a second outer surface; the SEM average pore size of the first outer surface is 1-80 nm; and the SEM average pore size of the first outer surface is smaller than the SEM average pore size of the second outer surface; the ultrafiltration layer and the transition layer are formed by a cellulose polymer, and the substrate layer is formed by a non-natural polymer microporous membrane; the binding layer includes a cellulose polymer and a non-natural polymer; in the binding layer, the cellulose polymer forms a first fiber, and the non-natural polymer forms a second fiber, the first fiber and the second fiber are entangled with each other to form a porous structure, and adjacent first fibers and second fibers are separated from each other to form a gap for fluid to pass through;

[0010] The non-natural polymer is any one of sulfone polymers, nylon and polyvinylidene fluoride.

[0011] The ultrafiltration membrane provided by the present invention is a composite membrane made of multiple polymer materials, with each layer structure produced in separate steps. Compared with integrally formed membranes, the greatest advantage of composite membranes is that different membrane materials can be selected to prepare each layer structure, thereby optimizing the function of each layer and achieving ideal performance parameters for the membrane as a whole.

[0012] Along the direction of fluid flow, the main structure of the membrane of the present invention is an ultrafiltration layer, a transition layer, a binding layer and a substrate layer in sequence, wherein the ultrafiltration layer mainly plays a role in retaining substances, and one side of the ultrafiltration layer is a first outer surface (i.e., a liquid inlet surface), on which there are some holes with smaller pore sizes; it is well known that the size of the pore size is a key factor in being able to retain substances, and different pore sizes can retain substances of different particle sizes; after research, it was found that when the SEM average pore size of the first outer surface is 1-80nm, such a pore size is suitable for intercepting various biomolecules (such as antibodies and other substances) with a molecular weight of 1K-750K, which is conducive to obtaining a higher retention efficiency; at the same time, by purifying various biomolecules in the form of tangential flow, the shear force is small, thereby avoiding the denaturation and inactivation of biomolecules; and the presence of the transition layer plays a protective role for the ultrafiltration layer, preventing the fiber structure such as burrs on the binding layer from affecting or even destroying the membrane pore structure of the ultrafiltration layer, thereby affecting the overall retention efficiency of the membrane, and further ensuring that the ultrafiltration layer can efficiently retain the corresponding substances;

[0013] In the present invention, both the ultrafiltration layer and the transition layer are prepared from a cellulose polymer through phase inversion. Therefore, the ultrafiltration layer has a strong hydrophilicity and is not easily adsorbed by biomolecules such as antibodies, thereby ensuring a high yield of the product. In addition, only one type of film-forming polymer (i.e., the cellulose polymer) is present in the ultrafiltration layer and the transition layer, and no other film-forming polymers are present. Of course, the presence of very small amounts of solvents, pore-forming agents, and other substances is not excluded.

[0014] In the binding layer, there are two membrane-forming polymers, one is a cellulose polymer and the other is a non-natural polymer, which is any one of a sulfone polymer, nylon and polyvinylidene fluoride; the cellulose polymer forms the first fiber and the non-natural polymer forms the second fiber; surprisingly, the first fiber and the second fiber are not adhered to each other, the two fibers are entangled with each other to form a porous structure, and the adjacent first fibers and second fibers are separated from each other to form a gap for fluid to pass through, that is, a structure similar to "interlocking rings", and the existence of the gap and the separation of the two fibers make the fluid have less resistance and easier to pass through when passing through the binding layer, and the pressure loss is reduced, thereby greatly improving the overall flux of the membrane (faster flow rate), fast filtration speed and high economic benefits; in addition, we also found that the second fibers formed by other types of polymers cannot form a similar structure with the first fibers (made of cellulose materials). It is speculated that the generation of this structure is not only related to the preparation method, but also has a great relationship with the properties of the corresponding material itself, that is, not all materials can form the membrane structure required by the present invention. For example, polyolefin microporous membranes cannot form it.

[0015] In addition, we also found that ultrafiltration membranes tend to become brittle during long-term filtration, resulting in poor overall elasticity and even rupture, which leads to a significant waste of biological fluids. However, when the first and second fibers in the bonding layer are no longer adhered to each other but instead form an "interlocking" relationship, we were pleasantly surprised to find that the overall elastic modulus and elastic deformation of the filter membrane were significantly improved. This reduces the risk of the filter membrane becoming too brittle, thus ensuring a longer service life. Even after a long period of filtration, the membrane can still efficiently retain various substances and is less likely to rupture.

[0016] At the same time, the substrate layer is formed by a non-natural polymer microporous membrane (the microporous membrane in the present invention is a porous membrane with a nominal pore size greater than 0.1 μm). The substrate layer is used to support the ultrafiltration layer, ensuring that the membrane as a whole has good mechanical strength and high compressive strength, and is suitable for long-term stable filtration under high pressure; the substrate layer includes a second outer surface, and there are a certain number of holes with larger pore sizes on the second outer surface, which further ensures that the membrane as a whole has a faster flow rate and a faster filtration speed.

[0017] In the present invention, the non-directional tortuous path refers to a randomly oriented groove structure and / or a discretely distributed pore structure, and each non-directional tortuous path is interconnected; the SEM average pore size of the first outer surface can be measured by using a scanning electron microscope to characterize the morphology of the membrane structure, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually to measure and perform corresponding calculations; in the preparation process of the membrane, in the direction perpendicular to the thickness of the membrane (if the membrane is in the form of a flat membrane, the direction is the planar direction; if the membrane is in the form of a hollow fiber membrane, the direction is perpendicular to the radial direction), its various characteristics such as the pore size distribution are roughly uniform and basically consistent; therefore, the average pore size of a part of the area on the corresponding plane can be used to reflect the overall average pore size on the plane. When actually measuring, the membrane surface can be characterized by an electron microscope to obtain the corresponding SEM image. Since the pores on the membrane surface are roughly uniform, a certain area can be selected, such as 1μm 2 (1 μm times 1 μm) or 25 μm 2 (5μm multiplied by 5μm), the specific area size depends on the actual situation, and then the pore size of all holes in the area is measured using corresponding computer software or manually, and then calculated to obtain the average pore size of the surface; the pore area ratio of the inner surface is the ratio of the sum of the areas of all holes on the surface to the area of ​​the surface; of course, those skilled in the art can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only.

[0018] As a further improvement of the present invention, the thickness of the bonding layer is not less than 5 μm; the SEM average diameter of the second fibers is smaller than the SEM average diameter of the first fibers, and is not less than 10% of the SEM average diameter of the first fibers; the SEM average diameter of the first fibers is not less than 20% of the SEM average pore size of the bonding layer.

[0019] At present, the biggest problem of composite membranes is that the composite strength (peel strength) is not high, and the layers are easy to separate, especially the bonding layer and the transition layer in the present invention are easy to separate, which can easily lead to a greatly reduced service life and inability to filter for a long time. In addition, the pressure resistance is not high enough and cannot be filtered under high pressure (if conditions permit, the greater the pressure during membrane filtration, the faster the filtration speed, and the higher the economic benefit per unit time); and the composite membrane has the risk of delamination / layer separation during pleating, and the processing practicality is relatively low; and in the present invention, since there is a gap (non-adhesion) between the first fiber and the second fiber in the bonding layer, the risk of delamination is further increased; so how to reduce this risk? On the one hand, the present invention controls the thickness of the binding layer. Since the first fiber and the second fiber exist in the binding layer at the same time, the thicker the binding layer, the higher the composite strength of the composite membrane and the better the pressure resistance. The thickness of the binding layer in the present invention is not less than 5 μm, so that the composite strength of the composite membrane is high and not easy to separate, ensuring that the ultrafiltration membrane can filter under high pressure for a long time. Furthermore, by controlling the thickness of the first fiber and the second fiber, when the first fiber or the second fiber is too thin, there is a risk of separation, and the first fiber and the second fiber both have appropriate thickness. After research, it was found that the first fiber and the second fiber do not need to be the same thickness. In the binding layer, the first fiber needs to be The first fibers are relatively thick, and the SEM average diameter of the first fibers is not less than 20% of the SEM average pore size of the binding layer; the first fibers can be relatively thin, but not too thin, and the SEM average diameter of the first fibers is not less than 10% of the SEM average diameter of the first fibers. The first fibers and the second fibers of such thickness can further improve the overall composite strength of the membrane; that is, under the synergistic effect of the thicker binding layer and the first fibers and the second fibers of appropriate thickness, the filter membrane as a whole is guaranteed to have a high composite strength, and the layers are not easily separated. At the same time, it also has high tensile strength and compressive strength. When the fluid is impacted by high pressure, the composite membrane will not separate, and the composite membrane can still play an efficient retention role.

[0020] The SEM average pore size of the binding layer in the present invention can be understood as the pore size of the holes formed by the first fiber; it can also be understood as the average pore size of the holes in the non-natural polymer microporous membrane used as the substrate except the substrate layer when preparing the composite membrane.

[0021] As a further improvement of the present invention, the thickness of the bonding layer is 15-150 μm; the thickness of the bonding layer is 10%-80% of the overall thickness of the membrane.

[0022] In the binding layer, there are two film-forming polymers at the same time; while in the ultrafiltration layer, transition layer and substrate layer, there is only one film-forming polymer; therefore, the thickness of the binding layer will affect the composite strength of the membrane. In order to ensure that the membrane has high composite strength and tensile strength, the thickness of the binding layer is preferably 15-150 μm; at the same time, although there is a gap between the first fiber and the second fiber in the binding layer, the existence of the gap can greatly improve the flux of the membrane, but compared with the substrate layer, the fluid is still easily affected by the first fiber and the second fiber when flowing in the binding layer, which will also affect the flow rate of the membrane to a certain extent; therefore, as a preference, the thickness of the binding layer accounts for 10%-80% of the overall thickness of the membrane (the ratio of the thickness of the binding layer to the overall thickness of the membrane will not be too high), while ensuring that the overall membrane has high composite strength and tensile strength, further ensuring that the overall membrane has a faster flow rate.

[0023] The thickness of the binding layer and the thickness of the entire membrane can be calculated by characterizing the morphology of the membrane structure using a scanning electron microscope, and then using computer software (such as Matlab, NIS-Elements, etc.) or manual measurement; of course, those skilled in the art can also obtain the above parameters by other measurement methods (such as the overall thickness of the membrane can be obtained by freeze-drying the filter membrane and then measuring it with a measuring tool). The above measurement methods are for reference only.

[0024] As a further improvement of the present invention, the SEM average diameter of the first fiber is 0.5-10 μm, the ratio of the SEM average diameter of the second fiber to the SEM average diameter of the first fiber is 0.15-0.45; the ratio of the SEM average diameter of the first fiber to the SEM average pore size of the bonding layer is 0.25-0.7.

[0025] In addition to the thickness of the bonding layer, the thickness of the first fiber and the second fiber will also affect the composite strength and other properties of the membrane; when the first fiber or the second fiber is too thin, the composite membrane is at risk of delamination, or the compressive strength is too low and cannot withstand pressure; but when the first fiber or the second fiber is too thick, although the composite membrane does not have the risk of delamination, the mechanical strength will basically no longer increase at this time. At the same time, it is also found that the overall flow rate of the membrane will be reduced to a certain extent. This is because in the bonding layer, the overly thick first fiber and second fiber will have a certain obstruction to the movement of the fluid, resulting in a certain degree of reduction in the membrane flow rate. Therefore, the first fiber and the second fiber cannot be too thick; at the same time, further research found that the so-called thickness does not only consider the absolute value of the first fiber and the second fiber, but also the corresponding ratio; for example, when the ratio of the SEM average diameter of the first fiber to the SEM average pore size of the bonding layer is too high (for example, reaching 0.9 or even higher), even if the SEM average diameter of the first fiber is not very thick, then this At the same time, such a membrane structure also causes a certain obstruction to the movement of the fluid, thereby affecting the membrane flow rate; through continuous experimental research, we found that by setting the ratio of the second fiber SEM average diameter to the first fiber SEM average diameter to 0.15-0.45, and the ratio of the first fiber SEM average diameter to the binding layer SEM average pore size to 0.25-0.7, the two characteristics can further ensure that the filter membrane has a faster flow rate, a higher composite strength, is not easy to delaminate, and can efficiently retain substances of corresponding molecular weight under high pressure for a long time; in addition, the first fiber and the second fiber of appropriate thickness can also ensure that the membrane as a whole has a higher elastic modulus and higher elasticity, and will not rupture even if a certain amount of swelling occurs; because in some special applications (such as separating and purifying insulin), the volume of the high molecular polymer will expand in the solvent, which will lead to the rupture of the filter membrane, greatly reducing the service life and having poor economic benefits. The filter membrane of the present invention has better elasticity and resistance to swelling, and has a wider range of applications.

[0026] The SEM average diameter of the first fibers and the second fibers can be measured by using a scanning electron microscope to characterize the morphology of the membrane structure, and then using computer software (such as Matlab, NIS-Elements, etc.) or manually to measure and perform corresponding calculations; for example, first use an electron microscope to characterize the membrane binding layer area to obtain a corresponding SEM image, the specific area size depends on the actual situation, and then use corresponding computer software or manually measure the diameters of all the first fibers and the second fibers in the area, and then calculate to obtain the SEM average diameter of the first fibers and the second fibers in the area; of course, those skilled in the art can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only;

[0027] As a further improvement of the present invention, the SEM average distance of the gap between the first fibers and the second fibers is 0.1-4 μm; and the ratio of the average distance of the gap to the SEM average diameter of the second fibers is not less than 0.4.

[0028] The existence of the gap is conducive to the rapid passage of the fluid. The larger the SEM average distance of the gap, the faster the flow rate of the fluid in the binding layer, and then the faster the flow rate of the entire membrane, that is, the membrane as a whole has a faster filtration speed; therefore, the gap distance cannot be too low. After research, it was found that the gap distance is not less than 0.1μm, and the ratio of the gap distance to the second fiber diameter should be not less than 0.4. Under the action of such a membrane structure, it is more conducive to ensuring that the membrane as a whole has a fast flow rate; but when the gap is too large, the tensile strength and composite strength of the entire membrane will be greatly reduced. During high-pressure filtration, the filter membrane will be stratified or even ruptured, which will cause the fluid containing biological molecules to spill all over the ground, causing great waste; therefore, the SEM average distance of the gap in the present invention is not greater than 4μm, ensuring that the membrane as a whole still has high tensile strength and composite strength.

[0029] As a further improvement of the present invention, the ratio of the SEM average distance of the gap to the SEM average pore size of the bonding layer is 0.1-0.6; the SEM average distance of the gap to the SEM average diameter of the second fiber is 0.5-5.

[0030] In addition to controlling the absolute distance of the gap, after research, it is preferred to control the ratio of the gap distance to the average pore size of the binding layer within a reasonable range, thereby further improving the various properties of the membrane; further, it was surprisingly found that when the ratio of the SEM average distance of the gap to the SEM average pore size of the binding layer is 0.1-0.6, it is beneficial to ensure that the overall flow rate of the membrane is faster, while also helping to ensure the overall mechanical strength of the membrane; in addition, this ratio is also beneficial to further ensure that the membrane has good elasticity and resistance to swelling. When the gap is too large, it will affect the stability of the pores inside the binding layer, which is prone to shrinkage or even collapse. The thickness of the second fiber is the key to maintaining the stability of the pores in the binding layer because, therefore, by controlling the SEM average distance of the gap and the SEM average diameter of the second fiber to be 0.5-5, the stability of the membrane pores in the binding layer is guaranteed, while ensuring the overall flow rate of the membrane, so that the fluid can pass through the binding layer quickly and stably.

[0031] As a further improvement of the present invention, the sum of the thickness of the ultrafiltration layer and the thickness of the transition layer is 1-30 μm; and the first water contact angle of the first outer surface is 15°-60° smaller than the first water contact angle of the second outer surface.

[0032] Compared with the binding layer and the substrate layer, the pore size of the pores in the ultrafiltration layer and the transition layer is relatively small. Therefore, when the sum of the thickness of the ultrafiltration layer and the transition layer is too large, it is easy to cause the overall flow rate of the filter membrane to be slow. The sum of the thickness of the ultrafiltration layer and the thickness of the transition layer of the present invention is 1-30μm, and the preferred sum of the thickness is 1-20μm, and more preferably, the sum of the thickness is 1.5-15μm, thereby ensuring that the membrane as a whole has a faster flow rate and good mechanical strength. In the prior art, it is always desirable that the compatibility (mainly referring to the hydrophilicity in the present invention) of the two materials of the ultrafiltration layer and the substrate layer be as high as possible, because if the compatibility is too low, the composite membrane will easily separate and the composite (peel) strength will be low. However, the inventors surprisingly discovered that the higher the hydrophilicity of the two materials, the better. When there is a certain difference in the hydrophilicity (compatibility) of the two materials, it is beneficial to prevent the two fibers in the binding layer from adhering to each other, thereby improving the elastic modulus of the composite membrane. It was also found that when the substrate layer (microporous membrane) is too hydrophilic, a "double skin" phenomenon will occur during the preparation of the filter membrane, resulting in a slower membrane flow rate. In the present invention, the hydrophilicity of the material is reflected by the first water contact angle, and the difference in the first water contact angle between the two outer surfaces of the composite membrane is used to reflect the difference in hydrophilicity between the two materials. Research has found that when the first water contact angle of the first outer surface is 15°-60° smaller than the first water contact angle of the second outer surface, it not only ensures that the overall membrane has a high composite strength and the layers are not easily separated; at the same time, it can further improve the overall elasticity (elastic modulus and elastic elongation) of the membrane and be more resistant to swelling. At the same time, the membrane as a whole also has a faster flow rate, and can quickly filter and purify the corresponding fluids containing various biological molecules for a long time.

[0033] As a further improvement of the present invention, the first water contact angle of the first outer surface is 15°-45°, and the roughness is 0.1-3 μm; the pore area ratio of the first outer surface is 1%-10%.

[0034] In the present invention, various fluids containing biological molecules are separated and purified by pores of a certain pore size on the first outer surface; since most biological molecules are currently protein substances, in order to ensure the yield of the product (protein), we hope that the first outer surface is sufficiently hydrophilic, so the first outer surface is formed by a cellulose polymer, and the size of the first water contact angle is used to characterize the hydrophilicity of the material surface. The first water contact angle refers to the test using water as the test liquid and a contact angle tester. When 10-100 microliters of water droplets are evenly dropped onto the material surface for an instant (within 0.4 seconds), a regular contact angle is formed; generally, the smaller the first water contact angle, the stronger the hydrophilicity of the material surface; when the first water contact angle of the material surface is less than 90°, it can be regarded as the surface of the material being hydrophilic, and further, the material is a hydrophilic material; through testing, it was found that the first water contact angle of the first outer surface was 15°-45°, which further and more specifically illustrates that the first outer surface is sufficiently hydrophilic and is not easy to adsorb protein, ensuring that the filter membrane has a high product yield;

[0035] In addition, it was found that the pore area ratio of the first outer surface was 1%-10% (preferably 3%-8%), that is, the number of pores on the first outer surface was relatively small and dense. Such a pore area ratio and the SEM average pore size of the first outer surface jointly ensured the retention efficiency, ensuring that the ultrafiltration membrane could fully and effectively retain substances with a molecular weight of 1-750K; in addition, after research, it was found that the first outer surface should not be too smooth, because when the first outer surface is too smooth, concentration polarization is very likely to occur, which causes the pores on the first outer surface to be blocked after only a short filtration time, thereby causing the membrane flow rate to drop rapidly; at the same time, the first outer surface should not be too rough, because biological molecules are very fragile. When the surface is too rough, the biological molecules (proteins) will be broken and the product yield will be greatly reduced; the roughness tester was used to test the roughness of the first outer surface, and it was found that the roughness of the first outer surface was 0.1-3μm, which was relatively smooth, which not only ensured the product yield, but also the concentration polarization phenomenon on the first outer surface would not be very obvious, and various fluids could be filtered quickly for a long time.

[0036] As a further improvement of the present invention, the thickness of the ultrafiltration layer is 0.1-5 μm; the ultrafiltration layer contains ultrafiltration fibers forming a porous structure, and the SEM average diameter of the ultrafiltration fibers is 25-65 nm.

[0037] The ultrafiltration layer is a key area in the membrane body for intercepting various biomolecules. To ensure the interception efficiency, the ultrafiltration layer will be relatively dense, with a relatively low internal porosity and slow fluid flow. However, when the ultrafiltration layer is too thick, not only will the interception efficiency not be further improved, but the overall flow rate of the membrane will also be slow, which cannot meet the needs of practical applications. Therefore, the thickness of the ultrafiltration layer cannot be too large. In the present invention, the thickness of the ultrafiltration layer is 0.1-5μm, preferably 0.5-4μm, which ensures that biomolecules of corresponding molecular weights are efficiently and fully intercepted while ensuring that the membrane as a whole has a faster flow rate.

[0038] There are a number of ultrafiltration fibers in the ultrafiltration layer. The presence of these ultrafiltration fibers ensures the stability of the pores inside the ultrafiltration layer. The pores are not easy to collapse or shrink, thereby ensuring that the filter membrane can filter fluid under high pressure for a long time; and makes the membrane as a whole have higher mechanical strength.

[0039] The thickness of the ultrafiltration layer and the SEM average diameter of the ultrafiltration fiber (the thickness of the fiber cross section can be considered as the diameter of the fiber) can be obtained by using a scanning electron microscope to characterize the morphology of the corresponding area of ​​the membrane structure, and then using computer software (such as Matlab, NIS-Elements, etc.) or manual measurement to calculate and measure; of course, those skilled in the art can also obtain the above parameters by other measurement methods, and the above measurement methods are for reference only;

[0040] As a further improvement of the present invention, the thickness of the transition layer is 0.5-28 μm, which is 1.5-10 times the thickness of the ultrafiltration layer; and the thickness of the transition layer is 0.05-0.5 times the thickness of the bonding layer.

[0041] The presence of the transition layer mainly plays a protective role for the ultrafiltration layer, preventing the surface of the microporous membrane used in the present invention from being not smooth enough, and still having a small amount of burrs and other fiber structures; secondly, the transition layer can further support the ultrafiltration layer, further ensuring the stability of the pores in the ultrafiltration layer; therefore, the transition layer needs to have a certain thickness; but the transition layer cannot be too thick, because the average pore size of the transition layer is generally smaller than the average pore size of the binding layer and the substrate layer (microporous membrane). When the transition layer is too thick, the overall flow rate of the membrane will be reduced to a certain extent; in the present invention, by controlling the thickness of the transition layer to 0.5-28μm, preferably 1-20μm, it not only supports and protects the ultrafiltration layer, but also helps the filter membrane to have a good flow rate as a whole; in addition, the thickness of the transition layer is further controlled to be 1.5-10 times the thickness of the ultrafiltration layer, and the thickness of the transition layer is controlled to be 0.05-0.5 times the thickness of the binding layer. Under the joint action of these characteristics, it is further guaranteed that the filter membrane has higher mechanical strength and faster flow rate.

[0042] As a further improvement of the present invention, the transition layer has support fibers forming a porous structure, and the SEM average diameter of the support fibers is 30-95 nm;

[0043] The ratio of the SEM average diameter of the support fibers to the SEM average diameter of the ultrafiltration fibers is 1.1-2;

[0044] The ratio of the SEM average diameter of the ultrafiltration fiber to the SEM average diameter of the second fiber is 8%-30%.

[0045] In order to ensure the stability of the pores in the transition layer and at the same time enable the transition layer to provide sufficient support to the ultrafiltration layer; the supporting fibers need to have an appropriate thickness. After research, the SEM average diameter of the supporting fibers is 30-95nm, which can not only ensure the stability of the pores inside the transition layer itself, but also effectively protect and support the ultrafiltration layer, thereby ensuring the stability of the fluid flow rate; further research found that the ultrafiltration fibers cannot be too thick, because too thick ultrafiltration fibers will affect the fluid movement and affect the membrane flow rate; therefore, the ratio of the SEM average diameter of the supporting fibers to the SEM average diameter of the ultrafiltration fibers is controlled to be 1.1-2, and the ratio of the SEM average diameter of the ultrafiltration fibers to the SEM average diameter of the second fibers is controlled to be 8%-30%. Under the joint action of these two characteristics, it is further ensured that the membrane as a whole has high mechanical strength and filtration stability, and can filter efficiently for a long time; therefore, the filter membrane is particularly suitable for application in the field of ultrafiltration.

[0046] As a further improvement of the present invention, the SEM average pore size of the transition layer is 100-1000 nm; and the ratio of the SEM average pore size of the transition layer to the SEM average pore size of the bonding layer is 0.04-0.4.

[0047] When the pore size in the transition layer is too large, on the one hand, the mechanical properties of the membrane as a whole cannot be guaranteed, and on the other hand, it cannot provide good support and protection for the ultrafiltration layer; and when the pore size in the transition layer is very small, it will affect the overall flow rate of the membrane. Therefore, it is necessary to further control the average pore size of the transition layer, and at the same time, control the ratio of the average pore size of the transition layer to the average pore size of the binding layer within a reasonable range; after research, by making the SEM average pore size of the transition layer 100-1000nm (preferably 200-800nm); at the same time, making the SEM average pore size of the transition layer and the SEM average pore size of the binding layer 0.04-0.4, it is further ensured that the membrane as a whole has a good flow rate, and can also support and protect the ultrafiltration layer for a long time, ensuring that filtration can be carried out stably for a long time.

[0048] As a further improvement of the present invention, in the transition layer, the SEM average pore size of the membrane pores increases continuously from the area close to the first outer surface to the area close to the bonding layer; the SEM average pore size change gradient in the transition layer is 50-500nm / 1μm.

[0049] When the filter membrane has high retention efficiency and good mechanical strength, people always hope that the flow rate of the membrane is as fast as possible, because this can quickly filter various biological molecular fluids; and in order to achieve this demand, we found that the pore size gradient of the transition layer can be changed, that is, the pore size of the transition layer close to the ultrafiltration layer side is smaller, for example, to maintain the stability of the pores in the ultrafiltration layer; and the pore size of the transition layer close to the binding layer side is relatively large, which can further make the membrane as a whole not only have higher mechanical properties, but also have a faster flow rate; at the same time, under the synergistic effect of transition fibers of a certain thickness, the overall strength of the membrane is ensured, and the fluid is ensured to flow stably and smoothly inside the membrane for a long time; at the same time, it can also make the fluid flow at a faster speed inside the membrane.

[0050] As a further improvement of the present invention, the SEM average pore size of the second outer surface is 0.5-20 μm; the first water contact angle of the second outer surface is 40°-85°, and the roughness is 6-12 μm.

[0051] Because most of the ultrafiltration membrane of the present invention is the substrate layer, the pore diameter inside the substrate layer will have a great influence on the membrane flow rate, so the pore diameter inside the substrate layer cannot be too small; in the present invention, the average pore diameter of the second outer surface can characterize the pore diameter size of the substrate layer to a certain extent. After research, the SEM average pore diameter of the second outer surface is 0.5-20μm, which is conducive to the membrane having a faster flow rate; further, in order to ensure the composite strength of the composite membrane, the compatibility between the two composite materials is also good. In the present invention, the hydrophilicity of the non-natural polymer microporous membrane is characterized by the size of the first water contact angle of the second outer surface. The first water contact angle is 40-85°, which is relatively hydrophilic, which is conducive to ensuring the overall composite strength of the membrane, and the layers are not easy to separate; at the same time, the roughness of the second outer surface is 6-12um, which is not so smooth, so it is easy to touch and perform corresponding processing, which is not easy to affect the filtration performance of the filter membrane, and the processing is relatively easy.

[0052] As a further improvement of the present invention, the thickness of the ultrafiltration membrane is 150-300 μm; the ultrafiltration membrane has a standard molecular weight cut-off of 1K-750K; the tensile strength of the ultrafiltration membrane is not less than 10 MPa;

[0053] Under the conditions of pressure of 0.68 bar and temperature of 25°C, the time required for 50 ml of water to pass through a 100K filter membrane with a diameter of 47 mm is no more than 400 seconds.

[0054] When the thickness of the membrane is too small, the mechanical strength of the membrane will be low; when the thickness of the membrane is too large, the filtration time will be too long and the time cost will be too high; since the filter membrane of the present invention is a composite membrane, the pore size in most areas is relatively large. In order to ensure the mechanical properties, the overall thickness of the membrane is relatively thick. After research, its thickness is suitable for 150-300μm, which ensures that the filter membrane not only has high mechanical strength, but also has a short filtration time and low time cost; the ultrafiltration membrane of the present invention has a retention efficiency of more than 90% for substances with a molecular weight of 1kD-750kD, and the retention efficiency is high, which shows that the membrane is particularly suitable for biological purification and meets the needs of practical applications; the protein yield of this membrane is not less than 90%, which shows that the effective substance protein in the fluid is not easily adsorbed on the membrane. On the one hand, it will not block the membrane pores, ensuring that the filter membrane still has a high service life, and on the other hand, it ensures that the content of various proteins of the effective substance in the fluid changes very little, and the protein is basically not lost, and the economic benefits are guaranteed. An important indicator for evaluating the mechanical strength of a filter membrane is the tensile strength of the filter membrane. Under certain conditions, the greater the tensile strength of the filter membrane, the better the mechanical strength of the filter membrane. The wet tensile strength of the filter membrane of the present invention is not less than 10 MPa (measured under wet membrane conditions), has a large tensile strength, good mechanical properties, and high industrial practical value, which can fully meet market demand. At the same time, by conducting a flow rate test on the filter membrane, it is shown that the flow rate of the filter membrane is large, the filtration time is short, and the time cost is low.

[0055] On the other hand, the present invention also provides a method for preparing a cellulose composite ultrafiltration membrane, comprising the following steps:

[0056] S1: preparing a casting solution, wherein the casting solution comprises the following materials in parts by weight: 10-30 parts of a cellulose polymer; 40-60 parts of a polar solvent; and 20-40 parts of a pore-forming agent; the cellulose polymer is at least one of nitrocellulose, cellulose acetate, and regenerated cellulose; and the casting solution has a viscosity of 6,000-30,000 cps;

[0057] S2: casting, casting the casting solution onto the non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is any one of sulfone polymer, nylon and polyvinylidene fluoride; the first water contact angle of the outer surface of the non-natural polymer microporous membrane is less than 90°;

[0058] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification, the phase separation solidification duration is 5-60s, and a membrane is obtained; the coagulation bath is water;

[0059] S4: placing the formed film in a sodium hydroxide aqueous solution for hydrolysis, and washing it after hydrolysis to form a solid film.

[0060] As a further improvement of the present invention, the cellulose acetate is selected from at least one of cellulose diacetate, cellulose triacetate, cellulose acetate butyrate and cellulose acetate propionate;

[0061] The polar solvent is at least one of acetone, dioxane, dimethylacetamide, N-methylpyrrolidone, acetic acid, propionic acid, butyric acid and valeric acid.

[0062] The pore-forming agent is at least one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol.

[0063] As a further improvement of the present invention, the PMI average pore size of the microporous membrane is 0.22 μm-10 μm; the porosity is 40-80%, and the thickness is 80-300 μm.

[0064] As a further improvement of the present invention, the concentration of the sodium hydroxide aqueous solution in S4 is between 0.01 mol / L and 1 mol / L; the hydrolysis time is between 40 min and 200 min, and the hydrolysis temperature is between 30° C. and 80° C.

[0065] As a further improvement of the present invention, the solid membrane is cross-linked with a water-soluble cross-linking agent in an alkaline environment, and washed with water after the cross-linking is completed to obtain an ultrafiltration membrane; wherein the cross-linking agent is at least one of a halogenated epoxide, a dihalogenated alkane, and a dihalogenated alcohol; the cross-linking time is 20-400 minutes, and the temperature is 30°C-60°C.

[0066] When preparing the composite membrane of the present invention, a casting solution is first prepared, which includes a membrane-forming material cellulose polymer, a polar solvent and a hydrophilic additive; wherein the cellulose polymer is at least one of nitrocellulose, cellulose acetate and regenerated cellulose, and further the cellulose acetate is selected from at least one of cellulose diacetate, cellulose triacetate, cellulose acetate butyrate and cellulose acetate propionate. Due to its own characteristics, the filter membrane prepared by the cellulose polymer is highly hydrophilic and is almost not easy to adsorb protein, ensuring the product yield, and is therefore particularly suitable for the purification of biomolecules; and the polar solvent is at least one of acetone, dioxane, dimethylacetamide, N-methylpyrrolidone, acetic acid, propionic acid, butyric acid and valeric acid, which is used to fully dissolve the cellulose polymer and form a uniform and stable casting solution; the pore-forming agent is at least one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol. The addition of the pore-forming agent can effectively control the viscosity of the system, inhibit the formation of macropores in the membrane during the phase separation process, and effectively improve the stability of the membrane flow rate; in addition The invention can greatly improve the hydrophilicity of the film-forming membrane, so that the filter membrane has high hydrophilicity and low protein adsorption; by adjusting the types and proportions of cellulose polymers, polar solvents and pore-forming agents, the casting liquid has an appropriate viscosity of 6000-30000 cps. The viscosity of the casting liquid will have a great influence on the structure and performance of the filter membrane finally formed, such as affecting the pore size, thickness, flow rate, etc. of the filter membrane; thereby ensuring that the filter membrane finally obtained has an appropriate thickness and an ideal membrane pore structure and pore size, which is then used to purify biological molecules; in addition, in order to ensure the composite strength, part of the casting liquid needs to penetrate into the base membrane-non-natural polymer microporous membrane; if the viscosity of the casting liquid is too high, the casting liquid has poor fluidity and is difficult to penetrate into the microporous membrane, so that the composite strength will be very low and it will be difficult to meet the needs of actual use; the viscosity of the casting liquid of the present invention can ensure that the casting liquid fully penetrates the microporous membrane, ensures the composite strength of the filter membrane, and makes the filter membrane have strong mechanical properties and can filter fluids efficiently and stably for a long time;

[0067] After the casting solution is prepared, the casting solution is then cast onto the non-natural polymer microporous membrane to form a liquid film; the casting solution can be manually cast (for example, by pouring, casting or spreading on a casting surface by hand) or automatically cast (for example, pouring or otherwise casting on a moving bed); a variety of equipment known in the art can be used for casting. Casting equipment includes, for example, a mechanical coater, which includes a coating knife, a doctor blade or a spray / pressurization system. As known in the art, a variety of casting speeds are suitable, for example, a casting speed of about 2-6 feet per minute (fpm), etc. The specific casting speed depends on the situation;

[0068] As one of the key points of the present invention, the selection of substrate is very important. In order to form two non-adhesive fibers in the filter membrane binding layer, the first thing to do is to select the type of substrate (microporous membrane). Because the properties of microporous membranes formed by different types of polymers are very different, there is no comparability, and there are also large differences in compatibility with cellulose polymers. After research, it was found that sulfone polymer (at least one of polyethersulfone, polysulfone and polyarylsulfone) microporous membrane, nylon microporous membrane, PVDF microporous membrane are more suitable as base membranes; further, it is necessary to control the hydrophilicity of the substrate (microporous membrane). The microporous membrane needs to be relatively hydrophilic (the first water contact angle of the outer surface is less than 90°). The microporous membrane with such characteristics makes it relatively easy for the casting liquid to invade the microporous membrane, thereby subsequently forming a thicker binding layer to ensure composite strength (in the present invention, since the casting liquid has a suitable viscosity, when the casting liquid is cast on the microporous membrane, the casting liquid will pass through the holes in the microporous membrane and enter the inside of the microporous membrane). In some areas, the area where the casting liquid enters is called the binding layer, and the area where the casting liquid does not enter the microporous membrane is called the base material layer); the other side of the microporous membrane has good hydrophilicity, which can make the coagulation bath enter the microporous membrane more quickly, and make the casting liquid quickly separate from the other side (the side away from the air), thereby forming an ideal ultrafiltration layer, transition layer and binding layer; that is, a base membrane with such characteristics and a suitable casting liquid, under certain phase separation conditions, can easily obtain an ultrafiltration membrane with fast flow rate and high mechanical strength; as a preference, we will also control the PMI average pore size, porosity and thickness of the microporous membrane; wherein the PMI average pore size is 0.22μm-10μm; the porosity is 40-80%, and the thickness is 80-300μm. By selecting a more excellent microporous membrane, it is further ensured that the casting liquid can enter the microporous membrane with a suitable thickness, thereby ensuring the composite strength of the film, and the layers are not easily separated; at the same time, it is also beneficial to improve the flow rate and tensile strength of the filter membrane;

[0069] Then phase separation solidification, the microporous membrane coated with liquid film is immersed in water for phase separation solidification, the phase separation solidification duration is 5-60s, by selecting the appropriate casting liquid and the appropriate phase separation time, the casting liquid is properly phase separated to ensure the formation of the ideal membrane pore size

[0070] The film is placed in a sodium hydroxide aqueous solution for hydrolysis, and then washed to form a solid film; wherein the concentration of the sodium hydroxide aqueous solution is 0.01-0.1 mol / L, the hydrolysis temperature is 30-80° C., and the hydrolysis time is 40-200 minutes; and the solid film is washed after hydrolysis; the solid film has better hydrophilicity and lower non-specific adsorption of proteins, thereby further improving protein yield and improving economic benefits;

[0071] Preferably, the hydrolyzed solid membrane is placed in an alkaline environment (pH 9-12) and cross-linked with a water-soluble cross-linking agent (cross-linking agent concentration is 5%-15%), wherein the cross-linking agent is at least one of halogenated epoxides, dihalogenated alkanes, and dihalogenated alcohols; the cross-linking time is 20-400 minutes, and the temperature is 30°C-60°C; during the cross-linking modification process, the hydroxyl groups in the solid membrane react with functional groups such as epoxy and halogen, thereby making the membrane structure more mechanically strong and less prone to swelling, while also improving the membrane's alkali resistance and extending its service life. At the same time, it is more conducive to the efficient retention of small molecular weight biomolecules (such as 3K and 5K biomolecules).

[0072] Beneficial effects of the present invention: The present invention provides a cellulose composite ultrafiltration membrane, comprising a main body, wherein one side surface of the main body is a first outer surface, and the other side surface is a second outer surface; along the direction of fluid flow, the main body is sequentially composed of an ultrafiltration layer, a transition layer, a binding layer and a substrate layer, the ultrafiltration layer includes a first outer surface, the substrate layer includes a second outer surface, and the SEM average pore size of the first outer surface is 1-80nm; it is used for efficiently intercepting biomolecules of 1K-750K; the ultrafiltration layer and the transition layer are formed of a cellulose polymer, which has strong hydrophilicity and is not easy to adsorb proteins, thereby ensuring that the membrane pores are not easily clogged and the product yield is ensured; the substrate layer is formed of a non-natural polymer microporous membrane , which is used to play a supporting role; in the binding layer, the cellulose polymer forms a first fiber, and the non-natural polymer forms a second fiber. The first fiber and the second fiber are entangled with each other to form a porous structure, and the adjacent first fibers and the second fibers are separated from each other to form a gap for fluid to pass through; the non-natural polymer is any one of sulfone polymers, nylon and polyvinylidene fluoride; the existence of the gap greatly improves the flow rate of the filter membrane, ensuring that the filter membrane can quickly separate and purify various biomolecular fluids, with high economic benefits; the preparation method provided by the present invention can conveniently, quickly and effectively prepare the above-mentioned cellulose composite ultrafiltration membrane. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is a scanning electron microscope (SEM) image of the first outer surface of the ultrafiltration membrane prepared in Example 3, wherein the magnification is 20K×;

[0074] Figure 2 This is a scanning electron microscope (SEM) image of the binding layer in the cross section of the ultrafiltration membrane prepared in Example 3, with a magnification of 5K×; (where 1 is the first fiber, 2 is the second fiber, and 3 is the hole in the binding layer)

[0075] Figure 3 This is a scanning electron microscope (SEM) image of the ultrafiltration layer and the transition layer in the cross section of the ultrafiltration membrane prepared in Example 3, where the magnification is 20K×;

[0076] Figure 4 This is a scanning electron microscope (SEM) image of the bonding layer in the cross section of the ultrafiltration membrane obtained in Example 4, with a magnification of 2K×; (where 1 is the first fiber and 4 is the gap)

[0077] Figure 5 This is a scanning electron microscope (SEM) image of the first outer surface of the ultrafiltration membrane obtained in Example 9, wherein the magnification is 50K×;

[0078] Figure 6 This is a scanning electron microscope (SEM) image of the first outer surface of the ultrafiltration membrane prepared in Comparative Example 1, wherein the magnification is 50K×;

[0079] Figure 7 This is a scanning electron microscope (SEM) image of the binding layer in the entire cross section of the ultrafiltration membrane prepared in Comparative Example 1, where the magnification is 500×;

[0080] Figure 8 This is a scanning electron microscope (SEM) image of the binding layer in the cross section of the ultrafiltration membrane obtained in Example 1, where the magnification is 5K×. DETAILED DESCRIPTION

[0081] To more clearly illustrate the overall concept of this application, the following examples are provided in detail. Unless otherwise specified, the raw materials and equipment used to prepare the filter membranes in the following examples are commercially available. The structure and morphology of the filter membranes were characterized using a Hitachi S-5500 scanning electron microscope.

[0082] Example 1

[0083] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0084] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 18 parts of cellulose diacetate; 48 parts of polar solvent acetone; 30 parts of pore-forming agent polyvinyl alcohol; the casting solution viscosity is 18000 cps;

[0085] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PES; the PMI average pore size of the microporous membrane is 2 μm and the thickness is 220 μm;

[0086] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification, the phase separation solidification duration is 30s, and a film is obtained;

[0087] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L for hydrolysis, the hydrolysis time is 120 min, the hydrolysis temperature is 60° C., and after hydrolysis, washing is performed to form a solid film.

[0088] Example 2

[0089] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0090] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 20 parts of cellulose triacetate; 50 parts of polar solvent dioxane; 32 parts of pore-forming agent polyvinyl pyrrolidone; the casting solution viscosity is 22000 cps;

[0091] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PVDF; the PMI average pore size of the microporous membrane is 4 μm and the thickness is 220 μm;

[0092] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 32 seconds to obtain a film;

[0093] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L for hydrolysis, the hydrolysis time is 140 min, the hydrolysis temperature is 60° C., and after hydrolysis, washing is performed to form a solid film.

[0094] Example 3

[0095] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0096] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 22 parts of cellulose triacetate; 52 parts of dimethylacetamide, a polar solvent; and 34 parts of polyethylene glycol, a pore-forming agent; the casting solution viscosity being 24,000 cps;

[0097] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PES; the PMI average pore size of the microporous membrane is 2.5 μm and the thickness is 240 μm;

[0098] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 38 seconds to obtain a film;

[0099] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.2 mol / L for hydrolysis, the hydrolysis time is 160 min, the hydrolysis temperature is 65° C., and after hydrolysis, washing is performed to form a solid film.

[0100] By the attached Figure 2It can be seen that in the bonding layer, the first fiber and the second fiber are entangled with each other to form a porous structure, and the adjacent first fibers and the second fibers are separated from each other to form a gap for fluid to pass through, ensuring that the filter membrane has a faster flow rate, quickly purifies the corresponding fluid, and makes the filter membrane have a higher elastic modulus and better elasticity; at the same time, the first fiber and the second fiber have appropriate thickness, ensuring the composite strength and tensile strength of the filter membrane; ensuring that the filter membrane can filter the fluid efficiently for a long time.

[0101] Example 4

[0102] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0103] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 24 parts of cellulose diacetate; 54 parts of polar solvent N-methylpyrrolidone; 36 parts of pore-forming agent polyvinyl alcohol; the casting solution viscosity is 26000 cps;

[0104] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is nylon; the PMI average pore size of the microporous membrane is 5 μm and the thickness is 240 μm;

[0105] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 40 seconds to obtain a film;

[0106] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.2 mol / L for hydrolysis, the hydrolysis time is 180 min, the hydrolysis temperature is 65° C., and after hydrolysis, washing is performed to form a solid film.

[0107] By the attached Figure 4 It can be seen that in the bonding layer, adjacent first fibers and second fibers are separated from each other to form a gap for fluid to pass through, ensuring that the filter membrane has a faster flow rate, quickly purifies the corresponding fluid, and makes the filter membrane have a higher elastic modulus and better elasticity.

[0108] Example 5

[0109] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0110] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 26 parts of nitrocellulose; 56 parts of acetic acid as a polar solvent; 38 parts of polyvinyl pyrrolidone as a pore-forming agent; the casting solution viscosity being 28,000 cps;

[0111] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PVDF; the PMI average pore size of the microporous membrane is 6 μm and the thickness is 250 μm;

[0112] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 48 seconds to obtain a film;

[0113] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L for hydrolysis, the hydrolysis time is 100 min, the hydrolysis temperature is 55° C., and after hydrolysis, washing is performed to form a solid film.

[0114] Example 6

[0115] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0116] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 28 parts of cellulose acetate butyrate; 58 parts of polar solvent propionic acid; 40 parts of pore-forming agent polyethylene glycol; the casting solution viscosity is 30,000 cps;

[0117] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is nylon; the PMI average pore size of the microporous membrane is 8 μm and the thickness is 260 μm;

[0118] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 58 seconds to obtain a film;

[0119] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.5 mol / L for hydrolysis, the hydrolysis time is 80 min, the hydrolysis temperature is 45° C., and after hydrolysis, washing is performed to form a solid film.

[0120] Example 7

[0121] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0122] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 16 parts of nitrocellulose; 46 parts of butyric acid as a polar solvent; 28 parts of polyethylene glycol as a pore-forming agent; the casting solution viscosity being 15,000 cps;

[0123] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PVDF; the PMI average pore size of the microporous membrane is 1.5 μm and the thickness is 200 μm;

[0124] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 25 seconds to obtain a film;

[0125] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.08 mol / L for hydrolysis, the hydrolysis time is 120 min, the hydrolysis temperature is 55° C., and after hydrolysis, washing is performed to form a solid film.

[0126] Example 8

[0127] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0128] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 15 parts of cellulose acetate propionate; 44 parts of polar solvent valeric acid; 26 parts of pore-forming agent polyvinyl alcohol; the casting solution viscosity is 12000 cps;

[0129] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PES; the PMI average pore size of the microporous membrane is 1 μm and the thickness is 200 μm;

[0130] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 20 seconds to obtain a film;

[0131] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.06 mol / L for hydrolysis, the hydrolysis time is 100 min, the hydrolysis temperature is 50° C., and after hydrolysis, washing is performed to form a solid film.

[0132] Example 9

[0133] A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0134] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 14 parts of cellulose diacetate; 42 parts of polar solvent acetone; 24 parts of pore-forming agent polyvinyl pyrrolidone; the casting solution viscosity is 10000 cps;

[0135] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PES; the PMI average pore size of the microporous membrane is 0.5 μm and the thickness is 180 μm;

[0136] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 15 seconds to obtain a film;

[0137] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.05 mol / L for hydrolysis, the hydrolysis time is 80 min, the hydrolysis temperature is 45° C., and after hydrolysis, washing is performed to form a solid film.

[0138] Example 10 A method for preparing a cellulose composite ultrafiltration membrane comprises the following steps:

[0139] S1: preparing a casting solution, the casting solution comprising the following materials in parts by weight: 12 parts of cellulose triacetate; 40 parts of polar solvent dioxane; 22 parts of pore-forming agent polyvinyl pyrrolidone; the casting solution viscosity being 8000 cps;

[0140] S2: Casting, casting the casting solution onto a non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is PES; the PMI average pore size of the microporous membrane is 0.22 μm and the thickness is 160 μm;

[0141] S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification. The phase separation solidification lasts for 8 seconds to obtain a film;

[0142] S4: placing the formed film in a sodium hydroxide aqueous solution with a concentration of 0.03 mol / L for hydrolysis, the hydrolysis time is 60 min, the hydrolysis temperature is 40° C., and after hydrolysis, washing is performed to form a solid film.

[0143] S5: placing the hydrolyzed solid membrane in an alkaline environment of pH = 10 and cross-linking with a water-soluble cross-linking agent, and washing it after the cross-linking is completed to obtain an ultrafiltration membrane; wherein the cross-linking agent is epichlorohydrin, the concentration of the cross-linking agent in the aqueous solution is 10%, the cross-linking time is 150 minutes, and the temperature is 45°C.

[0144] Comparative Example 1: The PES microporous membrane in Example 1 was replaced with a UPE microporous membrane, and the other conditions remained unchanged to prepare the corresponding ultrafiltration membrane. The structure and morphology of the membrane were characterized by scanning electron microscopy. Figure 6-8 ; By attaching Figure 8 It can be seen that in the bonding layer of the membrane cross section, the fibers formed by the cellulose polymer and the fibers formed by the UPE will adhere to each other, resulting in a significant decrease in the membrane flux.

[0145] Comparative Example 2: The hydrophilic PES microporous membrane in Example 1 is replaced with a hydrophobic PES microporous membrane, that is, the first water contact angle of the outer surface of the hydrophobic PES microporous membrane is greater than 90°, which is about 100° in the present invention; the other conditions remain unchanged, and the preparation is carried out to obtain the corresponding ultrafiltration membrane; during the preparation process, since the microporous membrane is very hydrophobic, water is not easy to enter the microporous membrane, thereby helping the casting liquid to separate into phases; this results in the pore size of the membrane in the transition layer of the ultrafiltration membrane being too large and the ideal first fiber not being formed in the binding layer, which in turn makes the overall mechanical properties of the membrane too low and impractical.

[0146] Comparative Example 3: The mass parts of cellulose diacetate in the casting solution of Example 1 were replaced from 18 parts to 35 parts, then the casting solution viscosity changed from 18000 cps to 35000 cps, and the average pore size of the PMI of the PES microporous membrane was adjusted from 2 μm to 0.1 μm. The other conditions remained unchanged, and the corresponding ultrafiltration membrane was prepared; during the preparation process, the casting solution was very viscous and had poor fluidity. At the same time, the pore size of the PES microporous membrane was very small, which resulted in the casting solution being almost unable to penetrate into the microporous membrane, and the binding layer required by the present invention could not be formed, let alone a thick binding layer. As a result, the overall mechanical properties of the membrane were too low, and it was not practical.

[0147] 1. Structural characterization

[0148] The membrane structure of the filter membrane obtained in each example was characterized by scanning electron microscopy to obtain the required data; the specific results are shown in the following table:

[0149] Table 1: Corresponding features on the first outer surface

[0150]

[0151] Table 2 - Corresponding characteristics of ultrafiltration layer and transition layer

[0152]

[0153]

[0154] Table 3 - Corresponding characteristics of the bonding layer

[0155]

[0156] Table 4 - Corresponding Features and Film Thicknesses on the Second External Surface

[0157]

[0158] As can be seen from Tables 1-4, the cellulose composite ultrafiltration membranes prepared in Examples 1-10 all have ideal membrane structures, and have suitable pore sizes on their first outer surfaces, which are suitable for intercepting biomolecules of different molecular weights (1-750K), thereby purifying various biomolecules; in the binding layer, the first fibers formed by the cellulose polymer and the second fibers formed by the non-natural polymer are entangled with each other to form a porous structure, and the adjacent first fibers and second fibers are separated from each other to form a gap for fluid to pass through, which greatly improves the overall filtration speed of the membrane (faster flow rate), reduces the mass transfer resistance, and at the same time makes the filter membrane have a good elastic modulus; further, by adjusting the thickness of the binding layer, the thickness of the first fibers and the second fibers, it is ensured that the membrane as a whole has a high composite strength and tensile strength, so that the filter membrane can filter efficiently for a long time.

[0159] Performance characteristics

[0160] Filtration accuracy test: The interception efficiency of the filter membrane obtained in each example was tested; wherein: the molecular weight of the substance intercepted by Example 1 and Example 2 is 100K; the molecular weight of the substance intercepted by Example 3 and Example 4 is 300K; the molecular weight of the substance intercepted by Example 5 is 500K; the molecular weight of the substance intercepted by Example 6 is 750K; the molecular weight of the substance intercepted by Example 7 is 50K; the molecular weight of the substance intercepted by Example 8 is 30K; the molecular weight of the substance intercepted by Example 9 is 10K; the molecular weight of the substance intercepted by Example 10 is 3K;

[0161] Flow rate test: Under a certain pressure, at a temperature of 25°C, 50 ml of the test solution, deionized water, passes through a filter membrane with a diameter of 47 mm. The pressure for Examples 1-6 and Comparative Example 1 was 0.68 bar; the pressure for Examples 7-10 was 3.8 bar. The specific test results are shown in the following table:

[0162]

[0163]

[0164] The cellulose composite ultrafiltration membranes prepared in Examples 1-10 of the present invention purify various biomolecules by tangential flow filtration; their molecular weight cutoffs range from 3K to 750K, and their retention efficiencies are all greater than 90%, ensuring efficient retention of biomolecules of various molecular weights; and flow rate tests (comparing Example 1 with Comparative Example 1) show that the membranes have a relatively fast flow rate, i.e., are capable of rapidly filtering fluids containing biomolecules, with high economic benefits.

[0165] The composite membrane prepared in Example 1 was further tested. The composite membrane prepared in Example 1 was used to separate and purify a 0.2% BSA solution. After one hour of continuous purification, the flow rate was tested using deionized water. It was found that the flow rate remained relatively fast with a time of 250 seconds.

[0166] Furthermore, tensile tests showed that the wet tensile strength of the cellulose composite ultrafiltration membranes prepared in Examples 1-10 of the present invention was no less than 10 MPa, indicating high mechanical properties and strong processing practicability. Elastic modulus tests (using a universal tensile testing machine) were also conducted on Examples 1-4 and Example 10, revealing that their elastic moduli were all greater than 200 MPa, indicating strong elasticity and resistance to swelling. Even after prolonged filtration, the membranes remained intact and could still efficiently filter various fluids. Example 10 can be used to purify fluids containing insulin, thereby obtaining high-concentration insulin.

[0167] In addition, after the protein yield test (which can be tested according to the protein yield test method used in China CN201010154974.7 - Ultra-porous membrane and its preparation method, or other methods), the protein yield of the filter membrane is greater than 90%, and a higher protein yield can be obtained, with high economic benefits.

[0168] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiment. All technical solutions based on the concept of the present invention are within the scope of protection of the present invention. It should be noted that for those skilled in the art, various improvements and modifications that do not depart from the principles of the present invention should also be considered within the scope of protection of the present invention.

Claims

1. A cellulose composite ultrafiltration membrane comprising a main body having a non-directional tortuous path therein, wherein one side surface of the main body is a first outer surface and the other side surface is a second outer surface, characterized in that: The main body comprises an ultrafiltration layer, a transition layer, a bonding layer, and a substrate layer in the order of fluid flow, the ultrafiltration layer including a first outer surface, and the substrate layer including a second outer surface; the first outer surface has a SEM average pore size of 1-80 nm; and the first outer surface has a SEM average pore size smaller than the second outer surface; The ultrafiltration layer and the transition layer are formed of cellulose polymers, the substrate layer is formed of a non-natural polymer microporous membrane; the bonding layer includes cellulose polymers and non-natural polymers; In the binding layer, the cellulose polymer forms first fibers, and the non-natural polymer forms second fibers, the first fibers and the second fibers are entangled with each other to form a porous structure, and adjacent first fibers and second fibers are separated from each other to form gaps for fluid to pass through; The non-natural polymer is any one of sulfone polymer, nylon and polyvinylidene fluoride; The first water contact angle of the second outer surface is less than 90°; There is an interlocking structure between the first fibers and the second fibers.

2. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The thickness of the bonding layer is not less than 5 μm; the SEM average diameter of the second fibers is smaller than the SEM average diameter of the first fibers, and is not less than 10% of the SEM average diameter of the first fibers; the SEM average diameter of the first fibers is not less than 20% of the SEM average pore size of the bonding layer.

3. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The thickness of the bonding layer is 15-150 μm; the thickness of the bonding layer is 10%-80% of the overall thickness of the membrane.

4. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The SEM average diameter of the first fibers is 0.5-10 μm, the ratio of the SEM average diameter of the second fibers to the SEM average diameter of the first fibers is 0.15-0.45; and the ratio of the SEM average diameter of the first fibers to the SEM average pore size of the bonding layer is 0.25-0.

7.

5. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The average SEM distance of the gaps between the first fibers and the second fibers is 0.1-4 μm; and the ratio of the average distance of the gaps to the average SEM diameter of the second fibers is not less than 0.

4.

6. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The ratio of the SEM average distance of the gap to the SEM average pore size of the bonding layer is 0.1-0.6; The SEM average distance between the gaps and the SEM average diameter of the second fibers is 0.5-5.

7. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The sum of the thickness of the ultrafiltration layer and the thickness of the transition layer is 1-30 μm; the first water contact angle of the first outer surface is 20°-60° smaller than the first water contact angle of the second outer surface.

8. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The first water contact angle of the first outer surface is 15°-40°, and the roughness is 0.1-3 μm; the pore area ratio of the first outer surface is 1%-10%.

9. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The thickness of the ultrafiltration layer is 0.1-5 μm; ultrafiltration fibers forming a porous structure are provided in the ultrafiltration layer, and the average SEM diameter of the ultrafiltration fibers is 25-65 nm.

10. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The thickness of the transition layer is 0.5-28 μm, which is 1.5-10 times the thickness of the ultrafiltration layer; and the thickness of the transition layer is 0.05-0.5 times the thickness of the bonding layer.

11. The cellulose composite ultrafiltration membrane according to claim 9, characterized in that: The transition layer has support fibers forming a porous structure, and the SEM average diameter of the support fibers is 30-95 nm; The ratio of the SEM average diameter of the support fibers to the SEM average diameter of the ultrafiltration fibers is 1.1-2; The ratio of the SEM average diameter of the ultrafiltration fiber to the SEM average diameter of the second fiber is 8%-30%.

12. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The SEM average pore size of the transition layer is 100-1000 nm; the ratio of the SEM average pore size of the transition layer to the SEM average pore size of the bonding layer is 0.04-0.

4.

13. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: In the transition layer, the SEM average pore size of the membrane pores increases continuously from the area close to the first outer surface to the area close to the bonding layer; the SEM average pore size change gradient in the transition layer is 50-500nm / 1μm.

14. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The SEM average pore size of the second outer surface is 0.5-20 μm; the first water contact angle of the second outer surface is 40°-85°, and the roughness is 6-12 μm.

15. The cellulose composite ultrafiltration membrane according to claim 1, characterized in that: The thickness of the ultrafiltration membrane is 150-300 μm; the ultrafiltration membrane has a standard molecular weight cut-off of 1K-750K; The tensile strength of the ultrafiltration membrane is not less than 10 MPa; Under the conditions of pressure of 0.68 bar and temperature of 25°C, the time required for 50 ml of water to pass through a 100K filter membrane with a diameter of 47 mm is no more than 400 seconds.

16. A method for preparing a cellulose composite ultrafiltration membrane according to claims 1 to 15, characterized in that: The following steps are involved: S1: preparing a casting solution, wherein the casting solution comprises the following materials in parts by weight: 10-30 parts of a cellulose polymer; 40-60 parts of a polar solvent; and 20-40 parts of a pore-forming agent; the cellulose polymer is at least one of nitrocellulose, cellulose acetate, and regenerated cellulose; and the casting solution has a viscosity of 6,000-30,000 cps; S2: casting, casting the casting solution onto the non-natural polymer microporous membrane to form a liquid film; the non-natural polymer is any one of sulfone polymer, nylon and polyvinylidene fluoride; the first water contact angle of the outer surface of the non-natural polymer microporous membrane is less than 90°; S3: Phase separation solidification, immersing the microporous membrane coated with the liquid film in a coagulation bath for phase separation solidification, the phase separation solidification duration is 5-60s, and a membrane is obtained; the coagulation bath is water; S4: placing the formed film in a sodium hydroxide aqueous solution for hydrolysis, and washing it after hydrolysis to form a solid film.

17. The method for preparing a cellulose composite ultrafiltration membrane according to claim 16, characterized in that: The cellulose acetate is selected from at least one of cellulose diacetate, cellulose triacetate, cellulose acetate butyrate and cellulose acetate propionate; The polar solvent is at least one of acetone, dioxane, dimethylacetamide, N-methylpyrrolidone, acetic acid, propionic acid, butyric acid and valeric acid; The pore-forming agent is at least one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol.

18. The method for preparing a cellulose composite ultrafiltration membrane according to claim 16, characterized in that: The PMI average pore size of the microporous membrane is 0.22 μm-10 μm; the porosity is 40-80%, and the thickness is 80-300 μm.

19. The method for preparing a cellulose composite ultrafiltration membrane according to claim 16, wherein: The concentration of the sodium hydroxide aqueous solution in S4 is between 0.01 mol / L and 1 mol / L; the hydrolysis time is between 40 min and 200 min, and the hydrolysis temperature is between 30° C. and 80° C.

20. The method for preparing a cellulose composite ultrafiltration membrane according to claim 16, wherein: The solid membrane is cross-linked with a water-soluble cross-linking agent in an alkaline environment, and then washed with water to obtain an ultrafiltration membrane; the cross-linking agent is at least one of halogenated epoxides, dihalogenated alkanes and dihalogenated alcohols; the cross-linking time is 2-40 minutes, and the temperature is 30°C-80°C.

Citation Information

Patent Citations

  • Ultrafiltration membrane and manufacturing method

    CN101816898B

  • Cellulosic ultrafiltration membrane

    CN1108853C

  • Composite ultrafiltration membrane

    EP0596411A3

  • RC ultrafiltration membrane and preparation method thereof

    CN112657346A

  • Bridged cellulose laminated semipermeable film and its production

    JP1991068431A